Pengaruh Hardiness Dan Motivasi Kerja Intrinsik Terhadap Kesiapan Kerja Pada Mahasiswa Akhir - Putri, Mutiara Rachmanda; Hadi, Cholichul (CV RIFAINSTITUT, 2023)
Final-year student opportunities to prepare themselves to enter the world of work due to the pandemic are limited. In fact, work readiness is needed to compete in entering the post-pandemic world of work. This study aims to determine whether hardiness and intrinsic work motivation affect work readiness in final-year students. The method used is quantitative survey research using the Dispositional Resilience Scale-15 (α = 0.798), the Multidimensional Work Motivation Scale (α = 0.859), and the Work Readiness Scale (α = 0.961). As a result, the hardiness factor and intrinsic work motivation affect the work readiness of final-year students. That is, the higher the hardiness and intrinsic work motivation, the higher the work readiness one has.